Integrating network and transfer metrics to optimize transfer efficiency and experiment workflows. Issue 5 (December 2015) - McKee, S.; Babik, M.; Campana, S.; Girolamo, A. Di; Wildish, T.; Closier, J.; Roiser, S.; Grigoras, C.; Vukotic, I.; Salichos, M.; De, Kaushik; Garonne, V.; et al.
Abstract: The Worldwide LHC Computing Grid relies on the network as a critical part of its infrastructure and therefore needs to guarantee effective network usage and prompt detection and resolution of any network issues, including connection failures, congestion, traffic routing, etc. The WLCG Network and Transfer Metrics project aims to integrate and combine all network-related monitoring data collected by the WLCG infrastructure. This includes FTS monitoring information, monitoring data from the XRootD federation, as well as results of the perfSONAR tests. The main challenge consists of further integrating and analyzing this information in order to allow the optimizing of data transfers and workload management systems of the LHC experiments. In this contribution, we present our activity in commissioning WLCG perfSONAR network and integrating network and transfer metrics: We motivate the need for the network performance monitoring, describe the main use cases of the LHC experiments as well as status and evolution in the areas of configuration and capacity management, datastore and analytics, including integration of transfer and network metrics and operations and support.